31 Motion corrected fetal cardiac mri increases diagnostic confidence in clinically challenging cases. (2nd February 2018) - Lloyd, DFA; Poppel, M van; Schultz, A; Pushparajah, K; Simpson, J; Amerom, JFP van; Kainz, B; Kuklisova-Murgasova, M; Vigneswaran, T; Charakida, M; Miller, O; Zidere, V; et al.
Abstract : Purpose: Prenatal MRI with novel motion-correction techniques has the potential to improve fetal diagnosis of congenital heart disease in clinically challenging cases. We sought to quantify the added value of MRI for fetuses with an unresolved echocardiographic diagnosis. Methods: Only patients with an incomplete fetal diagnosis were referred for MRI. Standard 'HASTE' images (2D) were acquired, and then reconstructed using a novel motion corrected slice-volume-registration algorithm to generate navigable 3D volumes (3DV) and segmented 3D models (3 DM) of the fetal vasculature. Two blinded clinicians were asked to independently score these data in order (2D-3DV-3DM); firstly according to a standard segmental approach, and secondly with regards to the areas of unresolved anatomy. Scores were given from 0 (no confidence) to 5 (high confidence). Results: 23 consecutive cases were analysed (14 with suspected abnormalities of the aortic and/or ductal arches, and 9 with abnormalities of the pulmonary vessels). In a structured approach for all patients, mean confidence scores from 2D-3DV-3DM data increased from 1.0–3.2*−3.7 for systemic venous anatomy; from 0.8–2.9*−3.6* for pulmonary arterial anatomy; from 0.8–2.6*−3.0 for pulmonary venous anatomy; and from 0.9–3.0*−4.6* for arch/ductal anatomy. In addressing the specific clinical question unresolved by echocardiography, diagnostic confidence increased from 0.7–2.9*−4.2*. Asterisks denote a P value of<0.001. All MRI findings were contemporaneously reported before birth, and confirmed postnatally in each case. Conclusion: Motion corrected slice-volume MRI techniques provide increased diagnostic confidence, during both structured and focussed assessment of fetal congenital heart disease. These novel techniques can offer a highly complementary adjunct to ultrasound in clinically challenging cases.